(untitled) (Bangladesh Medical Journal, 2022)
Gittleman syndrome (GS) is autosomal recessive renal tubulopathy caused by mutation of genes encoding protein for sodium chloride cotransporter and magnesium channel in the distal convoluted tubule.1 We present the case of a-20-years old female patient admitted in our Internal Medicine Department for recurrent hypokalaemia. She presented with recurrent quadriparesis. There was no history of taking inhaled salbutamol, insulin, steroid, diuretics and vomiting or diarrhoea. Investigations revealed hypokalaemia. Hypomagnesaemia, normal urinary excretion of sodium and potassium and hypercalcaemia. Her Serum albumin was within normal limit and renal function was normal. Diagnosis of Gittleman syndrome was established and was given potassium chloride and magnesium sulphate. Subsequently, the patient improved clinically and biochemically. Bangladesh Med J. 2021 Sept; 50(3): 49-51